Cultural Influences on Consumerism and Lifestyle Choices: An Analysis of College Students in Makawanpur, Nepal - Budhathoki, Drona (International Research Journal of MMC, 2025)
Cultural influences affect consumerism and lifestyle choices by shaping individual values, priorities, and social expectations. Traditions, norms, and media play a role in guiding preferences for products, fashion, and activities, creating unique consumer trends that reflect cultural identity and societal values. The main objective of this study is to examine the influence of cultural factors on consumer habits and lifestyle choices among youth students at Makawanpur Multiple College, specifically investigating how local and global cultural dynamics shape their consumption patterns and choices in Hetauda Sub-metropolitan City. The research adopts a descriptive research design. Primary data were collected directly from undergraduate and postgraduate students in the Management and Humanities faculties through structured interviews. Additionally, secondary data were obtained from previous studies, books, articles, bulletins, and journals. The study highlights key points of social behaviors among youth, focusing on friendship, consumer habits, and leisure activities, all influenced by gender and financial status. While wealthier students engage more in social activities, economic disparities limit others. Gender roles remain entrenched, with male students taking financial responsibility in social settings. Social media dominates youth culture, while literary reading declines, revealing evolving cultural patterns. This study emphasizes the implications of cultural influences in shaping consumer habits and lifestyle choices among youth, particularly in Hetauda. It highlights the impact of economic status, gender roles, and social media on social behaviors, revealing evolving cultural trends.